Overview of the seven wonders of the ancient world - Leonard, Melinda; Rafferty, John P. (Academic Video Online, 2013)
The Seven Wonders of the Ancient World: 1. Pyramids of Egypt; 2. Hanging Gardens of Babylon; 3. Statue of Zeus at Olympia; 4. Mausoleum at Halicarnassus; 5. Temple of Artemis (Diana) at Ephesus; 6. Colossus of Rhodes; 7. Pharos (lighthouse) of Alexandria.